Red cell distribution width and associated factors among hypertensive patients attending Arba Minch General Hospital, Southern Ethiopia: A comparative cross-sectional study - Orgeta Robsha; Selamu Girma; Teklu Teshome; Tesfaye Kanko (PLoS ONE, 2025)
Background Red cell distribution width (RDW) has been increasingly linked with cardiovascular and metabolic conditions. However, its clinical relevance in hypertension remains underexplored in Ethiopia. This study aimed to assess RDW levels, associated factors, and its potential utility in hypertension management. Methods An institution-based comparative cross-sectional study was conducted from November 2023 to January 2024 among 70 hypertensive patients and 70 age- and sex-matched normotensive controls. Hypertensive participants were consecutively recruited from the hypertension outpatient clinic, while controls were recruited from the general outpatient department using systematic random sampling. Data were collected using a pretested and structured interviewer-administered questionnaire via the KOBO Collect to obtain sociodemographic, lifestyle, and clinical information. Five milliliters of venous blood were drawn from each participant for hematological and biochemical analyses. Data were entered and analyzed using SPSS version 26.0. Independent t-test and Mann–Whitney U-test were used for group comparisons, multivariable logistic regression assessed associations, and Spearman correlation tested RDW versus hypertension duration. Receiver operating characteristic (ROC) curve analysis was performed to determine the predictive ability of RDW for detecting disease severity. A p-value < 0.05 was considered statistically significant. Results Hypertensive patients had significantly higher mean RDW values compared to normotensive controls (15.1 ± 2.0% vs. 13.0 ± 2.0%, p < 0.001). RDW was higher in hypertensive patients with stage II (16.35 ± 2.60%) and poorly controlled blood pressure (16.00 ± 2.10%) compared to stage I (14.95 ± 2.10%) and controlled blood pressure (14.70 ± 1.20%). RDW showed a positive but non-significant correlation with hypertension duration (rs = 0.127, P = 0.295) and demonstrated a predictive power of 74.1% for detecting hypertension severity at a cut-off value of 14.5%. RDW was significantly elevated among participants who consumed alcohol (AOR = 6.48; 95% CI: 1.92–21.85), chewed khat (AOR = 5.65; 95% CI: 1.06–29.9), or had elevated C-reactive protein (AOR = 5.90; 95% CI: 1.67–20.89) and serum creatinine (AOR = 4.35; 95% CI: 1.19–15.91). Conclusions A higher RDW reported among hypertensive patients compared to their counterparts, with RDW increasing across hypertension stages. These findings suggest a possible role of RDW as an indicator of hypertension progression. Therefore, assessing RDW may provide supportive information for the early identification and management of hypertension-related complications.